TEAM WORK DALAM KINERJA GURU - Fadillah, Ahmad Arif; Hadi, Awal Septian; Shafarida, Nurul Afni; Sari, Alfina Amanda; Luthfia; Nursabila, Putri Rizky; Asyifa, Syaqila Nur; Supriyanti; Utami, Angelia Fitria; Ramadini, Cantika (Transpublika Publisher, 2022)
One of the things that must be developed in the current era is teamwork. The success of the school is determined by each component in the school. Principals and teachers and staff must work in teams that are appropriate for their roles. This study aims to determine the effect of teamwork in teacher performance. The technique adopted is a literature review, in which the findings of several research publications conducted in the United States, the Netherlands, and Slovenia will be compared. Several articles, one of which discusses the respective roles between principals and teachers from several journal studies that they researched using literature studies. The findings of this article are that teamwork can be carried out by transformational leaders who have advantages in speaking and are able to stimulate teachers and others. Urgency in carrying out roles in a clear and coordinated manner with the framework of developing and working team functions (teamwork).